Rule-Level Verification of Business Process Transformations using CSP - Bisztray, Dánes; Heckel, Reiko (Electronic Communications of the EASST, 2007)
Business Process Reengineering is one of the most widely adopted techniques to improve the efficiency of organisations. Transforming process models, we intend to change their semantics in certain predefined ways, making them more flexible, more restrictive, etc.To understand and control the semantic consequences of change we use CSP to capture the behaviour of processes before and after the transformation. Formalising process transformations by graph transformation rules, we are interested in verifying semantic properties of these transformations at the level of rules, so that every application of a rule has a known semantic effect.It turns out that we can do so if the mapping of activity diagrams models into the semantic domain CSP is compositional, i.e., compatible with the embedding of processes into larger contexts.